Effects of rice husk charcoal on the resistance of Jali (Coix lacryma-jobi L.) to drought stress during generative phase - Qaanitatul Hakim Ipaulle; Didik Indradewa; Siti Nurul Rofiqo Irwan (Jurnal Ilmu Pertanian, 2023)
The production of jali (Coix lacryma-jobi L.) under stress can be increased by the application of a soil enhancer, called rice husk charcoal.  This study aimed to determine the effect of rice husk charcoal on the yield of jali plants under drought stress and to determine the minimum soil water content from the interval time of watering to ensure that plants can still produce grains. The treatment (interval time watering and weight of rice husk charcoal) was arranged in a split-plot design. The main plot was the interval time of watering, consisting of 3 levels: every two days, every four days, and every six days. The weight of rice husk charcoal as sub-plots consisted of 3 levels: 0 t ha⁻¹, 10 t ha⁻¹, and 20 t ha⁻¹. The data were analyzed using analysis of variance (ANOVA) and further tested using Duncan Multiple Range Test (DMRT) at a significance level of 5%. The results showed that rice husk charcoal could not increase the yield of jali plant under drought stress. Jali plants could still produce grains at a watering interval time of every six days with a minimum soil moisture content of 11.85%, or equivalent to 35.54% of field capacity.